Antifungal activity of shampoo formulated with water spinach (Ipomoea aquatica) ethanolic extract against Pityrosporum ovale - Aisali, Ledyta Asa; Genatrika, Erza; Budiman, Arif (Pharmacy Department, Faculty of Health Sciences, Jenderal Soedirman University, Purwokerto, Indonesia, 2024)
Background: Dandruff, primarily caused by Pityrosporum ovale, is a common scalp disorder, especially in tropical regions. Natural alternatives, such as water spinach (Ipomoea aquatica), are increasingly being explored for their antimicrobial properties due to their minimal side effects. Objective: This study aimed to formulate an anti-dandruff shampoo using ethanol extract of water spinach and evaluate its physical properties and antifungal activity against P. ovale. Results: The phytochemical screening of the water spinach extract confirmed the presence of polyphenols, flavonoids, and quinones, known for their antimicrobial properties. The shampoo formulations met pH and foam height standards and remained organoleptically stable over 28 days. However, viscosity decreased below the standard (<400 cps) after 28 days. The 4% extract formulation (F3) showed the highest antifungal activity with an inhibition zone of 10.01 mm, significantly greater than the negative control (p<0.05). Conclusion: Water spinach ethanol extract can be successfully formulated into a shampoo that meets most physical requirements and exhibits antifungal activity against P. ovale. The 4% extract formulation demonstrated the highest effectiveness, though viscosity stability requires further optimization.